Diagnosis of the Plinth Zone in Buildings Under Conservation Protection - Ksit, Barbara; Nowogońska, Beata (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of thermographic research make it possible to model the actual operating conditions of selected parts of building structures. The article presents diagnostic analyses using thermographic tests of plinth zones in historic buildings. The results of the research form the basis for making decisions on thermo-renovation projects, and in historic buildings these decisions are additionally conditioned by the need to meet conservation requirements.
Keywords: diagnostic test; thermal imaging surveys; plinth listed; historic building